2009
DOI: 10.1093/eurjhf/hfp136
|View full text |Cite
|
Sign up to set email alerts
|

Timing of eplerenone initiation and outcomes in patients with heart failure after acute myocardial infarction complicated by left ventricular systolic dysfunction: insights from the EPHESUS trial†

Abstract: AimsTo test the hypothesis that an earlier post-acute myocardial infarction (AMI) eplerenone initiation in patients with left ventricular systolic dysfunction (LVSD) and heart failure (HF) is associated with better long-term outcomes. Methods and resultsThe 6632 patients of the EPHESUS study were randomized from day 3 to 14 after the index AMI (median ¼ 7 days), of these 3319 were assigned to eplerenone. We analysed the differential effects of time-to-eplerenone initiation vs. placebo, based on the median time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 36 publications
2
51
0
7
Order By: Relevance
“…To determine whether the mechanism for the cardioprotective action of low dose MR antagonists required regulating ARC processing, we used the rat cardiomyocyte cell line (H9c2) since many of the characteristics of isolated primary cardiomyocytes are retained [8,9]. H9c2 cells were cultured in Dulbecco's modified Eagle's medium (DMEM) (Invitrogen) which contained 10% fetal bovine serum, L-glutamine (2 mM), penicillin (10 U/mL) and streptomycin (10 μg/mL) at 37°C in a humidified atmosphere with 5% CO 2 , and at ~90% confluence were harvested for experiments.…”
Section: Cell Culture Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether the mechanism for the cardioprotective action of low dose MR antagonists required regulating ARC processing, we used the rat cardiomyocyte cell line (H9c2) since many of the characteristics of isolated primary cardiomyocytes are retained [8,9]. H9c2 cells were cultured in Dulbecco's modified Eagle's medium (DMEM) (Invitrogen) which contained 10% fetal bovine serum, L-glutamine (2 mM), penicillin (10 U/mL) and streptomycin (10 μg/mL) at 37°C in a humidified atmosphere with 5% CO 2 , and at ~90% confluence were harvested for experiments.…”
Section: Cell Culture Studiesmentioning
confidence: 99%
“…2 Lowdose mineralocorticoid receptor (MR) antagonists have been shown clinically to reduce blood pressure, 3,4 particularly in resistant hypertension, and to substantially increase survival in heart failure, 5 heart failure after myocardial infarction, 6 and chronic systolic heart failure with mild symptoms. 7 Significant benefits follow when eplerenone is administered early (Ͻ7 days) after myocardial infarction 8 and experimentally at reperfusion. 9,10 Interestingly, MR antagonists added to standard treatment proved effective despite levels of plasma aldosterone in the physiological range.…”
mentioning
confidence: 99%
“…16 The drug was most effective when treatment was applied as early as possible. 17 It was effective in patients with diabetes mellitus 18 and in those with most severely impaired left ventricular function. 19 Eplerenone reduced mortality particularly in patients with predictors of high-risk factors, namely, in those with ejection fraction ≤ 30% or in patients with diabetes ( Figure 3).…”
Section: Severe Heart Failurementioning
confidence: 99%
“…Delyani et al [25] showed that MR antagonism did not improve infarct expansion in rats when started 24 h postinfarction. Of interest, in the clinical setting, better long-term outcomes were observed when eplerenone initiation started early after acute MI in patients with LV dysfunction and heart failure [26].…”
Section: Pharmacological Mr Blockadementioning
confidence: 99%